Metagenomic next-generation sequencing assists in the diagnosis of Cryptococcus pneumonia: Case series and literature review - Wang, Huifen; Yan, Su; Liu, Ying; Li, Yaoguang; Cui, Guangying; Ma, Xiaoxu (Frontiers in Public Health, 2022)
Background Pulmonary cryptococcosis (PC) was once thought to occur only in patients with immune deficiencies, such as tested positive for the Human Immunodeficiency Virus (HIV). However, in recent years, it has been discovered that more than half of the patients with PC in our nation are individuals with normal immune function. As more and more PC cases are recorded, our diagnosis and treatment approaches, as well as our understanding of PC, are gradually improving. In reality, most PC patients still have a high incidence of misdiagnosis on their initial visit. It is primarily linked to the diverse clinical manifestations, atypical imaging findings, and inaccurate diagnostic approaches. Methods The research was conducted from 2019 to 2020. We performed traditional microbiological testing and mNGS on sample from patients with fever of Pulmonary nodules or lung infections. Furthermore, we collected patients' baseline information, clinical features, laboratory and imaging examination results, diagnosis, treatment and outcome. In the end, we confirmed three cases of PC using biopsy and mNGS. Conclusion Our data demonstrates that mNGS can be utilized as an auxiliary method for PC diagnosis. Early mNGS aids in the identification of pathogens, enabling early diagnosis and treatment, as well as a reduction in the rate of misdiagnosis and illness progression.